CLEAN DRINKING WATER, GENDER EQUALITY AND WOMEN EMPOWERMENT: AN ANALYSIS - Sharma, Seema Kaushik; Pramila (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Clean drinking water is a critical issue linked to gender equality and women empowerment. One of the often overlooked aspects of this relationship is how water-related burdens and the gender pay gap in the workforce are intertwined. Women, especially in rural and developing areas, are disproportionately responsible for collecting water, which often takes up a considerable amount of time every day. This unpaid labor limits their opportunities for paid work, economic advancement, and career development, contributing to the gender pay gap. In many societies, women’s role in water management and infrastructure is undervalued, and their labor is often overlooked in formal economic measures. A multi-pronged approach is needed to address the gender pay gap in the context of water access and management. This abstract explains how improving access to clean water can help reduce the disproportionate burdens women face, increasing their ability to participate in the formal workforce and take advantage of economic opportunities. By shifting the responsibility for water collection from women to modern infrastructure, communities free up women’s time, allowing them to take up paid work and reduce the gender pay gap. Furthermore, empowering women to take on leadership roles in water management and governance can create more equitable systems that not only provide clean water but also advance gender equality in the labor market. Ultimately, tackling the gender pay gap requires addressing fundamental issues of unpaid labor, access to resources, and opportunities for women. Reducing the burden of water on women and promoting their participation in economic and decision-making processes are essential to creating a fairer, more just workforce and society.